P25 Assessment of salt intakes using spot urine samples; should it be abandoned in analytical epidemiological studies?. (13th September 2016) - McCarthy, LE; Harrington, J; Perry, I
Abstract : Background: A positive graded relationship between salt intake and blood pressure is well established. However, it has been recently suggested based on studies relying on spot urine samples that "low salt intake" (<7.5 g/day) might increase the risk of cardiovascular disease (CVD). The aim of this study was to compare the different methods of estimating salt intake from spot urine samples in a representative sample of middle aged men and women and to compare the CV risk profiles of those with low versus moderate-high sodium excretion. Methods: Secondary analysis of cross-sectional data from Phase II (2010) of the Cork and Kerry Diabetes and Heart Disease Study (Mitchelstown Cohort (IC: = 2, 047)) was conducted. Sodium excretion over 24-h was estimated from arithmetic extrapolation of spot samples using previously validated 24-h mean urine volume estimations and formula estimates based on the Kawasaki and INTERSALT formulas. Levels of agreement between formulae were assessed using Cohen's Kappa Statistic for Measuring Agreement, Spearman's Rank Correlation Coefficient and Bland-Altman Plots. Low sodium excretion was defined as being consistently in the lowest quartile of sodium excretion across all methods of estimating 24-h sodium intake. Results: Mean salt intake, based on arithmetic extrapolations, Kawasaki and INTERSALT estimates, was 12.1 g, 11.3 g and 9.9 g for males and 7.5 g, 9.4 g and 6.4 g for females, respectively. Agreement between methods of estimation was poor-moderate: Cohen's Kappa Statistic was <0.60 for all comparisons between formulae and bland-Altman plots illustrated poor agreement between formulae with mean differences ranging from −0.8 g to 1.2 g salt. Among those who were consistently in the lowest quartile of sodium excretion, low sodium excretion was significantly associated with underweight/normal BMI (p = 0.002), lower mean SBP (p = 0.005) and lower mean waist circumference (p = 0.000) among males, while low sodium excretion was significantly associated with higher education level (p = 0.018), moderate-high physical activity (p = 0.017), underweight/normal BMI (p = 0.000) and lower waist circumference (p < 0.001) among females. However, the strengths of these associations varied depending on which formula was applied to estimate 24-h sodium intake. Conclusion: Based on evidence from this study, the estimation of 24-h sodium intake from spot urine samples using formula-derived estimates is not reliable in examining the association between sodium and CVD risk factors. Associations between sodium excretion and CVD risk factors vary significantly depending on which method of estimation is used in analysis. Current studies suggesting associations between low salt intake and CVD will need to be replicated using 24 hr urine samples (currently the reference method for estimating salt intake).